2019
DOI: 10.1016/j.anl.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management for T1 and T2 external auditory canal cancer

Abstract: Objective: The purpose of this study was to clarify the impact of superficial parotidectomy and postoperative radiotherapy (PORT) for the surgical treatment of early stage squamous cell carcinoma (SCC) in external auditory canal (EAC). Materials and Methods: Thirty-seven patients with T1 (n=14) or T2 (n=19) SCC in EAC treated between 2000 and 2016 at Kobe University Hospital were enrolled in this study. Thirty-three patients were operated with sleeve resection or lateral temporal bone resection. Results: The 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
8
24
0
Order By: Relevance
“…Although there have been no large cohort studies due to its rarity, complete surgical resection is considered to be an optimal treatment (5). For this purpose, sleeve resection or lateral temporal bone resection (LTBR) is suitable for T1/T2 tumors that are localized to the EAC and EAC with bone erosion or with <0.5 mm soft tissue involvement, for which favorable outcomes have been reported (6,7). On the other hand, subtotal temporal bone resection (STBR) has been proposed as a standard surgery for advanced carcinoma, which is a more invasive and challenging approach than LTBR because of its anatomical complexity (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been no large cohort studies due to its rarity, complete surgical resection is considered to be an optimal treatment (5). For this purpose, sleeve resection or lateral temporal bone resection (LTBR) is suitable for T1/T2 tumors that are localized to the EAC and EAC with bone erosion or with <0.5 mm soft tissue involvement, for which favorable outcomes have been reported (6,7). On the other hand, subtotal temporal bone resection (STBR) has been proposed as a standard surgery for advanced carcinoma, which is a more invasive and challenging approach than LTBR because of its anatomical complexity (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…Of various head and neck cancers, it is reported that the early-stage nasal and paranasal carcinomas [3][4][5] and early-stage external auditory canal carcinomas (EACCa) [1,2] rarely develop regional LN metastasis or cervical lymph node metastases [6]. Such patients might be good candidates for stereotactic radiosurgery (SRS)/SRT as an upfront therapy instead of surgical extirpation as the initial therapy [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shinomiya et al [ 1 ] reported the good results of surgical treatment of early-stage EACC in 33 cases (T1, 14; T2, 19). All were SCC and were operated on with sleeve resection or lateral temporal bone resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of various head and neck cancers, it is reported that only 10-15% of early-stage nasal and paranasal carcinomas (NpNCa) have cervical lymph node (LN) involvement [14][15][16]. Also, patients with early-stage external auditory canal carcinomas (EACCa) rarely develop regional LN metastasis [17,18]. Such patients might be good candidates for SRS/SRT as an upfront therapy, instead of surgical extirpation, as the initial therapy.…”
Section: Early-stage Head and Neck Cancersmentioning
confidence: 99%